Analysis of Production Systems from an Islamic Economic Perspective - Supandi, Ach Faqih; Ashilah, Khittah; Agustin, Mawadatul Hifniyah; Hannan, Fais Faizul; Firdausi, Firdausi (Faculty of Islamic Economics and Business, UIN Prof. K. H. Saifuddin Zuhri Purwokerto, 2024)
Production activities are mandatory to meet all human needs and to utilize the availability of natural resources to meet all what is needed by humans by producing or processing them. Production is the initial activity in economic activity, production basically aims to produce goods and services or produce and add value to the use of goods and services. Production is not only an activity in meeting personal needs but also for prot. Production not only aims to create what does not exist into existence, but also to produce production activities that are empowered In Islam itself, it is also explained about being a good producer based on the production system in an Islamic economic perspective. Therefore, this journal aims to provide an overview and knowledge for the general public and especially for producers to understand the ow of Islam in explaining the production system and regulating it. The method used to describe this research is a qualitative descriptive method, meaning that the technique used in this research is a literature study that focuses on nding information from journals, books or other forms of writing.